Conservative Management or Cesarean Hysterectomy for Placenta Accreta Spectrum: The PACCRETA Prospective Study. Issue 1 (22nd March 2023) - Sentilhes, L.; Seco, A.; Azria, E.; Beucher, G.; Bonnet, M.P.; Branger, B.; Carbillon, L.; Chiesa, C.; Crenn-Hebert, C.; Dreyfus, M.; Dupont, C.; Fresson, J.; et al.
Abstract : ( Am J Obstet Gynecol . 2022;226:839.e1–24) Placenta accreta spectrum (PAS) is a phenomenon where trophoblasts attach or penetrate the myometrium and occasionally into adjacent organs. This can cause complications with delivery such as massive blood loss and multiple organ failure and is associated with high levels of maternal morbidity. PAS is occurring with increased frequency. The principal option for women with PAS is cesarean hysterectomy; however, alternative approaches include leaving the placenta in situ (conservative management), thus preserving the woman's fertility. Small prospective have demonstrated conservative management to be associated with improved outcomes but larger studies are needed. This study was designed to assess maternal recovery and outcomes after cesarean hysterectomy compared with conservative management.